Dynamic pricing and dual‐channel choice in the presence of strategic consumers. (17th January 2022) - Yu, Dongdong; Wan, Miyu; Luo, Chunlin
Abstract : This paper develops a dynamic pricing model to examine how strategic consumers affect the strategic interaction among firms under three dual‐channel formats, that is, direct selling dual‐channel, reselling dual‐channel, and agency selling dual‐channel. The results show that the retailer's selling prices display nonmonotonic relations to the acceptance of electronic channel. When strategic consumers have high patience, all firms prefer to decrease prices in both periods. The interaction of the acceptance of electronic channel and discount factor mediate the optimal mode choice for the firms. In most cases, the reselling dual‐channel and agency selling dual‐channel format are preferable for the retailer and the e‐retailer, respectively.